Regulation of autoimmune arthritis by the SHP-1 tyrosine phosphatase - Adrienn Markovics; Daniel M. Toth; Tibor T. Glant; Katalin Mikecz (Arthritis Research & Therapy, 2020)
Abstract Background The Src homology region 2 domain-containing phosphatase-1 (SHP-1) is known to exert negative regulatory effects on immune cell signaling. Mice with mutations in the Shp1 gene develop inflammatory skin disease and autoimmunity, but no arthritis. We sought to explore the role of SHP-1 in arthritis using an autoimmune mouse model of rheumatoid arthritis. We generated Shp1 transgenic (Shp1-Tg) mice to study the impact of SHP-1 overexpression on arthritis susceptibility and adaptive immune responses. Methods SHP-1 gene and protein expression as well as tyrosine phosphatase activity were evaluated in spleen cells of transgenic and wild type (WT) mice. WT and Shp1-Tg (homozygous or heterozygous for the transgene) mice were immunized with human cartilage proteoglycan (PG) in adjuvant, and arthritis symptoms were monitored. Protein tyrosine phosphorylation level, net cytokine secretion, and serum anti-human PG antibody titers were measured in immune cells from WT and Shp1-Tg mice. WT mice were treated with regorafenib orally to activate SHP-1 either before PG-induced arthritis (PGIA) symptoms developed (preventive treatment) or starting at an early stage of disease (therapeutic treatment). Data were statistically analyzed and graphs created using GraphPad Prism 8.0.2 software. Results SHP-1 expression and tyrosine phosphatase activity were elevated in both transgenic lines compared to WT mice. While all WT mice developed arthritis after immunization, none of the homozygous Shp1-Tg mice developed the disease. Heterozygous transgenic mice, which showed intermediate PGIA incidence, were selected for further investigation. We observed differences in interleukin-4 and interleukin-10 production in vitro, but serum anti-PG antibody levels were not different between the genotypes. We also found decreased tyrosine phosphorylation of several proteins of the JAK/STAT pathway in T cells from PG-immunized Shp1-Tg mice. Regorafenib administration to WT mice prevented the development of severe PGIA or reduced disease severity when started after disease onset. Conclusions Resistance to arthritis in the presence of SHP-1 overexpression likely results from the impairment of tyrosine phosphorylation (deactivation) of key immune cell signaling proteins in the JAK/STAT pathway, due to the overwhelming tyrosine phosphatase activity of the enzyme in Shp1-Tg mice. Our study is the first to investigate the role of SHP-1 in autoimmune arthritis using animals overexpressing this phosphatase. Pharmacological activation of SHP-1 might be considered as a new approach to the treatment of autoimmune arthritis.